A 2‐D tomographic model of the Juan de Fuca plate from accretion at axial seamount to subduction at the Cascadia margin from an active source ocean bottom seismometer survey. Issue 8 (14th August 2016) - Horning, G.; Canales, J. P.; Carbotte, S. M.; Han, S.; Carton, H.; Nedimović, M. R.; van Keken, P. E.
Abstract: We report results from a wide‐angle controlled source seismic experiment across the Juan de Fuca plate designed to investigate the evolution of the plate from accretion at the Juan de Fuca ridge to subduction at the Cascadia margin. A two‐dimensional velocity model of the crust and upper mantle is derived from a joint reflection‐refraction traveltime inversion. To interpret our tomography results, we first generate a plausible baseline velocity model, assuming a plate cooling model and realistic oceanic lithologies. We then use an effective medium theory to infer from our tomography results the extent of porosity, alteration, and water content that would be required to explain the departure from the baseline model. In crust of ages >1 Ma and away from propagator wakes and regions of faulting due to plate bending, we obtain estimates of upper crustal hydration of 0.5–2.1 wt % and find mostly dry lower crust and upper mantle. In sections of the crust affected by propagator wakes we find upper estimates of upper crustal, lower crustal, and upper mantle hydration of 3.1, 0.8, and 1.8 wt %, respectively. At the Cascadia deformation front, we find that the amount of water stored at uppermost mantle levels in the downgoing JdF plate is very limited (<0.3 wt %), with most of the water carried into the subduction zone being stored in the oceanic crust. Key Points: Ridge to trench 2‐D velocity model of the Juan De Fuca plate The mantle of the subducting JdF plate is dry to very mildly hydrated Propagator wakes are zones of enhanced hydration that may affect subduction zone processes